Asymptomatic SARS-CoV-2 Infection Is Common Among ART-Treated People With HIV. (1st August 2022) - Overton, Edgar T.; Weir, Isabelle R.; Zanni, Markella V.; Fischinger, Stephanie; MacArthur, Rodger D.; Aberg, Judith A.; Fitch, Kathleen V.; Frank, Michael; Albrecht, Helmut; Goodenough, Elliot; Rhame, Frank S.; Fichtenbaum, Carl J.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Limited data are available regarding asymptomatic COVID-19 among people with HIV (PWH). Data on a representative subset of PWH enrolled in Randomized Trial to Prevent Vascular Events in HIV, a global clinical trial, are presented here. Methods: Randomized Trial to Prevent Vascular Events in HIV is an atherosclerotic cardiovascular disease prevention trial among 7770 PWH on antiretroviral therapy. Beginning April 2020, targeted data on coronavirus disease 2019 (COVID-19) diagnosis and symptoms were collected during routine trial visits. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was defined as either COVID-19 clinical diagnosis or presence of SARS-CoV-2 Immunoglobulin G (IgG) or Immunoglobulin A (IgA) receptor binding domain protein (antispike) antibodies in the absence of prior COVID-19 vaccine. Results: The group (N = 2464) had a median age 53 years, 35% female sex, 47% Black or African American race, median CD4 count 649 c/mm 3, and 97% with HIV VL <400 cp/m. SARS-CoV-2 infection occurred in 318 persons (13%): 58 with clinical diagnosis and 260 with detectable antibodies. Of these PWH, 304 completed symptom questionnaires: 121 (40%) reported symptoms, but 183 (60%) were asymptomatic. PWH with asymptomatic SARS-CoV-2 infection were more likely to be from low-income or middle-income regions, of Black or African American race, older in age, and with higher atherosclerotic cardiovascular disease risk score. Symptomatic COVID was more common with obesity, metabolic syndrome, and low HDL levels. CD4 counts and HIV viral suppression rates were similar among PWH with symptomatic vs. asymptomatic COVID. Conclusions: Asymptomatic SARS-CoV-2 infection is common among antiretroviral therapy–treated PWH globally. We determined that 60% of infections in PWH were asymptomatic. HIV clinicians must remain vigilant about COVID-19 testing among PWH to identify asymptomatic cases.